113Cd NMR Experiments Reveal an Unusual Metal Cluster in the Solution Structure of the Yeast Splicing Protein Bud31p1. Issue 16 (20th February 2015) - van Roon, Anne‐Marie M.; Yang, Ji‐Chun; Mathieu, Daniel; Bermel, Wolfgang; Nagai, Kiyoshi; Neuhaus, David
Abstract Establishing the binding topology of structural zinc ions in proteins is an essential part of their structure determination by NMR spectroscopy. Using 113Cd NMR experiments with 113Cd‐substituted samples is a useful approach but has previously been limited mainly to very small protein domains. Here we used 113Cd NMR spectroscopy during structure determination of Bud31p, a 157‐residue yeast protein containing an unusual Zn3Cys9 cluster, demonstrating that recent hardware developments make this approach feasible for significantly larger systems.